Carbon monoxide poisoning - Shrestha, Sitaram (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Carbon monoxide (CO) poisoning may be suicidal, homicidal and in many cases it is accidental. Poisoning is due to formation of carboxyhaemoglobin, which interferes transfers of oxygen and leads to appearance of symptoms.1 Which are not specific and may similar to COVID19. Symptoms depends upon concentration of CO in surroundings. Antidote of CO is oxygen.